Effect of hot extrusion and T6 heat treatment on microstructure and mechanical properties of Al-10Zn-3.5Mg-2.5Cu nanocomposite reinforced with graphene nanoplatelets. (December 2018) - Mirjavadi, Seyed Sajad; Alipour, Mohammad; Hamouda, A.M.S.; Kord, S.; Koppad, Praveennath G; Abuzin, Yu. A.; Keshavamurthy, R.
Abstract: Al-10Zn-3.5Mg-2.5Cu/graphene nanocomposites were developed by a combination of liquid metallurgy and hot extrusion techniques. The effect of varying graphene content (0.1%, 0.3%, 0.7% and 1.0%) on microstructure and mechanical properties was studied in as cast, hot extruded and heat treatment conditions. The hot extruded nanocomposites showed uniform dispersion of graphene in matrix and mostly dispersed in the grain boundaries. With the increase in graphene content the grain size of as cast and hot extruded nanocomposites showed significant drop. The ultimate tensile strength of nanocomposites increased with the increase in graphene content up to 0.7% for both as cast and hot extruded conditions. Due to precipitation hardening the heat treated and hot extruded nanocomposites showed highest increment in strength. The fracture studies showed inter-dendritic cracking for alloy and mixed fracture mode failure for nanocomposites as main failure mechanisms.